The Effectiveness of Life Skills Training on Enhancement of Quality of Life and Coping Styles in Methadone Maintenance Therapy Members - Ali Beygi; Mahmood Shirazi; Mahdi Pasandide (Drug Control Headquarters, Research and Education Office, 2013)
Objective: This study aimed to examine the effectiveness of life skills training on enhancement of quality of life, and Coping Styles in Methadone maintenance Therapy members. Method: In this pseudo experimental study 64 males selected and assigned randomly in two groups (experimental and witness). Both groups completed quality of Life and Coping styles questionnaires in two phases as a pre and post test. Results: The results indicated that scores of experimental group was significantly higher on Task-oriented and Emotion-oriented. Also scores of experimental group was significantly higher on interpersonal relationship, physical health, and life requirements. Conclusion: It seems that life skills training in addiction patients enhance quality of life and effective coping styles.